2014
DOI: 10.1007/s00330-014-3512-3
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of focal-type autoimmune pancreatitis from pancreatic carcinoma: assessment by multiphase contrast-enhanced CT

Abstract: • f-AIP can mimic PC on imaging findings. • The differentiation of f-AIP from PC is important in patient management. • Some CT findings can be used to identify AIP. • The combination of CT findings will improve differentiation from PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 33 publications
1
38
0
4
Order By: Relevance
“…Contrast-enhanced CT and MRI are helpful for differential diagnosis of benign and malignant lesions based on characteristic vascularization patterns [13, 32, 33]. Several studies showed differences between pancreatic carcinoma and mass-forming focal pancreatitis using contrast-enhanced approaches [31, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced CT and MRI are helpful for differential diagnosis of benign and malignant lesions based on characteristic vascularization patterns [13, 32, 33]. Several studies showed differences between pancreatic carcinoma and mass-forming focal pancreatitis using contrast-enhanced approaches [31, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties of distinguishing autoimmune pancreatitis from pancreatic malignancies on CT have been reported previously, particularly in cases of focal autoimmune pancreatitis 6,7) , which shows partial pancreatic enlargement and abnormal enhancement that mimics pancreatic adenocarcinoma or hypovascular NET. In addition, negative cytology results do not exclude the possibility of pancreatic tumors, resulting in unnecessary pancreatic resections.…”
Section: Clinical Datamentioning
confidence: 91%
“…We investigated whether we could distinguish the 14 pancreatic cancer patients from the 34 autoimmune pancreatitis patients who were not diagnosed by EUS-FNA. For differential diagnosis, we used the capsule-like rim sign 26,[29][30][31][32][33] and narrowing of the main pancreatic duct without extension, 8,30,[34][35][36][37] which are characteristic indicators of autoimmune pancreatitis, as well as serum tumor markers (CEA, CA19-9). We reviewed the capsule-like rim sign by enhanced CT and determined the main pancreatic duct diameter by CT or magnetic resonance imaging (MRI).…”
Section: Validationmentioning
confidence: 99%